(untitled) (Scientific journal of the Fergana State University, 2023)
On the eve of the Soviet rule, the field of education, its condition, quantitative changes of schools, the unique features of the personnel training system, its consequences, effects and results on the culture of the Uzbek people. The nature of teaching in schools, the introduction of secular sciences, popularization of the Russian language were mentioned.